Testing the Efficacy of the Red-Light Purple-Light Games in Preprimary Classrooms in Kenya - Willoughby, Michael T.; Piper, Benjamin; King, Katherine Merseth; Nduku, Tabitha; Henny, Catherine; Zimmermann, Sarah (Frontiers in Psychology, 2021)
This study adapted and tested the efficacy of the Red-Light Purple-Light (RLPL) games for improving executive function (EF) skills in preprimary classrooms in Nairobi, Kenya. A cluster randomized controlled trial was used to evaluate the efficacy of the adapted RLPL intervention. Specifically, 24 centers (including 48 classrooms) were randomized to the RLPL or a wait-list control condition. Consistent with previous studies, participating classrooms delivered 16 lessons across an 8-week intervention period. A total of 479 children were recruited into the study. After exclusions based on child age and data quality, 451 and 404 children (90% retention) had completed computerized assessments of EF skills at pre- and posttest assessments, respectively. Children in the RLPL centers did not demonstrate any improvements in EF skills relative to their peers in the wait-list control condition (Cohen’s ds = -.14 to .03, all ps > .20). Exploratory tests of moderators (language of assessment, grade, school type, baseline ability) were also all null. Results are discussed with respect to measurement limitations and contextual factors that may explain the null results of RLPL on EF skills in young children in Kenya.